2011
DOI: 10.1155/2011/358493
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Epithelial-Stromal Interactions: Role of Interleukins 1 and 6

Abstract: Ovarian epithelial cancer is the most lethal gynecologic malignancy. The high mortality is attributed to the fact that most cases typically present in late stage when ovarian cancer (OC) has already spread beyond the ovary. Ovarian epithelial cancer cells are shed into intraperitoneal ascites and easily disseminate throughout the peritoneal cavity with preferential metastasis to the omentum, peritoneum, and local organs. Understanding how ovarian epithelial cells interact with and modulate their microenvironme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 104 publications
(121 reference statements)
0
11
0
1
Order By: Relevance
“…It has been shown that both normal and malignant epithelial ovarian cells along with activated immune cells in the stroma produce IL-1β. Moreover, constitutive production of IL-1β by ovarian carcinoma cells stimulates production of cytokines such as IL-6 [34]. To simulate what happens in ovarian tumors, we used IL-1β (10 ng/ml) to induce IL-6 expression in ovarian cancer cells and then examined whether minocycline can block the surge in IL-6 expression.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that both normal and malignant epithelial ovarian cells along with activated immune cells in the stroma produce IL-1β. Moreover, constitutive production of IL-1β by ovarian carcinoma cells stimulates production of cytokines such as IL-6 [34]. To simulate what happens in ovarian tumors, we used IL-1β (10 ng/ml) to induce IL-6 expression in ovarian cancer cells and then examined whether minocycline can block the surge in IL-6 expression.…”
Section: Resultsmentioning
confidence: 99%
“…In animal models, the expression of IL-8 is associated with increased tumorigenicity and ascites formation 71,72 . IL-6 has been shown to promote growth 70 , chemoresistance, tumour invasion 73 and angiogenesis 74,75 . High levels of IL-6 (REFS 69,76,77) and IL-10 (REF.…”
Section: Additional Properties Of Ascitesmentioning
confidence: 99%
“…It is known that the levels of these cytokines are substantially higher within the peritoneal fluid than in serum 2. Both ILs, as well as their receptors, are expressed at different levels within the epithelial cells of ovarian cancer of various malignancy grades 16,21,22. The tumor-promoting effect of these cytokines involves enhancement of anchorage-independent growth, proliferation, and angiogenesis as well as cellular adhesion and invasion 17,23.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 and IL-8 have long been identified as cytokines involved in the neoplastic process leading to the development of ovarian cancer. 21 Because this analysis focused on the levels of cytokines and growth factors within the peritoneal fluid of ovarian cancer patients, it included typical representatives of this class. It is known that the levels of these cytokines are substantially higher within the peritoneal fluid than in serum.…”
Section: Discussionmentioning
confidence: 99%